Wide Bandgap Semiconductor Technologies for Next-Generation Power Electronics: Materials, Devices, and Application Perspectives (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Silicon-based power semiconductors are starting to show their limits as high-power, high-frequency electronics get more common in things like electric cars, renewable energy, data centers, and phone networks. Silicon just can't handle the high voltages, quick switching, and heat that these systems need. Wide bandgap (WBG) semiconductors look like a solution because they handle electricity and heat a lot better.This paper takes a look at silicon carbide (SiC) and gallium nitride (GaN) semiconductors and how they can power the next wave of electronics. We'll check out what makes them work well, like how much energy it takes to get electrons moving, how much electric field they can take, how fast electrons move through them, and how well they conduct heat. We'll also break down how SiC MOSFETs and GaN HEMTs work, looking at their designs. SiC devices are great for high-voltage, high-power jobs, while GaN devices shine in systems that need high frequency and pack a lot of power into a small space. Recent tests show SiC MOSFET converters hitting 98–99% efficiency, and GaN converters running at over 500 kHz with power densities over 50 kW/L [14–16].We'll also look at where these materials are being put to work, like in electric car motors, renewable energy systems, power supplies, and phone networks, to show why they matter to industry. The paper also covers some of the current issues, like defects in the materials, how reliable the devices are, how tricky they are to make, and how much they cost. Besides that, we'll peek at some upcoming ultra-wide bandgap materials like gallium oxide and diamond, which might be used for super-high-voltage stuff in the future [19–20]. All in all, WBG semiconductors are going to be key in making power electronics more efficient, smaller, and able to handle heat in future energy and communication systems.